PENGARUH STRUKTUR KEPEMILIKAN, STRUKTUR MODAL, FREE CASH FLOW,TERHADAP KEBIJAKAN INISIASI DIVIDEN - Widya Jati Lestari (Universitas Catur Insan Cendekia (CIC) Cirebon, 2017)
Abstract Dividend policy is only one of the many policies owned companies that have implemented and realized, because no dividend, it is feared the shareholders will switch to another company that has been clear division of dividends. This study aims to determine the effect of capital structure, ownership structure, free cash flow, dividend policy and the companies that went public on the Indonesia Stock Exchange.The population in the study are all companies that went public on the Indonesia Stock Exchange 2000-2009 period as many as 158 companies. The samples were selected based on purposive sampling of companies that went public on the Indonesia Stock Exchange issued a policy period of 2000-2009 the initiation of dividends a year after an IPO obtained by 47 companies. This study uses path analysis techniques.The results showed that: 1) Capital Structure insignificant negative effect of Free Cash Flow; 2) Ownership Structure significant negative impact on Free Cash Flow; 3) Capital Structure significant negative effect on dividend policy; 4) Ownership structure is not significant negative effect on Dividend Policy; 5) Free Cash Flow significant positive effect on dividend policy. Keywords : Capital Structure, Cash, Dividend Policy.